Stove by a whale : Owen Chase and the Essex - Heffernan, Thomas Farel, 1933- (UPCC book collections on Project MUSE., 1981)
A documentation of the first sinking of a ship by a whale. This book contains a harrowing account by the ship's first mate of the survivors' three months adrift in small boats. A thrilling narrative that directly inspired Herman Melville's masterpiece Moby Dick.